2015
DOI: 10.3390/en8042587
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electric Fields on the Combustion Characteristics of Lean Burn Methane-Air Mixtures

Abstract: Abstract:In this work, the effects of the electric fields on the flame propagation and combustion characteristics of lean premixed methane-air mixtures were experimentally investigated in a constant volume chamber. Results show that the flame front is remarkably stretched by the applied electric field, the stretched flame propagation velocity and the average flame propagation velocity are all accelerated significantly as the input voltage increases. This indicates that the applied electric field can augment th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…The appearance of the ionic wind effect makes the flame surface unstable due to fluid dynamics. Fang et al and Duan et al used similar experimental devices to study the combustion under an electric field with the spherical flame method [26][27]. Experimental studies have found that the application of voltage can increase the stretching and burning rate of the flame.…”
Section: Spherical Flame Propagation Methodsmentioning
confidence: 99%
“…The appearance of the ionic wind effect makes the flame surface unstable due to fluid dynamics. Fang et al and Duan et al used similar experimental devices to study the combustion under an electric field with the spherical flame method [26][27]. Experimental studies have found that the application of voltage can increase the stretching and burning rate of the flame.…”
Section: Spherical Flame Propagation Methodsmentioning
confidence: 99%
“…Research on the effects of a dc field on a hydrocarbon flame has been done by many researchers [12][13][14][15][16][17][18][19]. Results have shown the electric field capable of increased lean blowoff limits, increased flame burning velocity, decreased emissions and soot formation, and enhanced flame stability.…”
Section: Nomenclaturementioning
confidence: 99%
“…Previous studies [30,31,38] have verified that our electrode arrangement could only produce an approximately uniform electric field between the ignition and the mesh electrode, and a u was about 0.7 in the main study zone for −2.5 kV and −5 kV electric field.…”
Section: Governing Equationsmentioning
confidence: 99%